Strategi Hotel Abadi Kota Serang dalam Mempertahankan Citra dan Reputasi Perusahaan - Rica Anggraini; Achmad Nashrudin Priatna; Noerma Kurnia Fajarwati; Eka Susilawati; Putri Handayani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the strategies implemented by Hotel Abadi in Serang City to maintain its image and reputation amidst the increasingly competitive hotel industry and pressures caused by the COVID-19 pandemic. A descriptive qualitative approach was used with a SWOT analysis technique to identify the strengths, weaknesses, opportunities, and threats facing the hotel. The results show that Hotel Abadi still relies on the strength of social relationships and loyalty of existing customers as reputation capital, but has not been able to manage its image comprehensively in accordance with the principles of image management theory. The communication strategies used are still conventional, such as banners and direct promotions, and have not yet touched on the realm of digital branding and professional management of customer feedback. On the other hand, the threat from new, more modern hotels that are more adaptive to technological developments is an urgent external challenge that requires a strategic response. Hotel Abadi must also pay more attention to service quality, not only from the physical side but also the overall customer experience. Given the rapid development of technology, management needs to formulate a more targeted and effective digital communication strategy to reach a wider audience through social media and websites. Hotel Abadi is advised to undertake a strategic transformation that is not only promotion-oriented, but also includes strengthening brand identity, improving service quality based on customer needs, and structured reputation management with an image management approach.